Dietary Diversity and Nutritional Status Among Rwandan Women Engaged in Agriculture: A Cross‐Sectional Study - Sunday François Xavier; Philemon Kwizera; Yves Didier Umwungerimwiza; Rutayisire Reverien; Kanimba Philbert; Ilinde Niyigena Delice; Maryse Umugwaneza (Wiley, 2024)
ABSTRACT Background Dietary diversity is crucial for nutritional adequacy, particularly among women of reproductive age who have increased nutritional needs due to menstruation, pregnancy, and lactation. This is especially important in addressing anemia in Rwanda, which poses significant health risks for both mothers and children. This study assessed the dietary diversity, nutritional status, and related factors among Rwandan women engaged in agriculture. Methods In 2022, a cross‐sectional study in Nyamagabe, Karongi, and Nyabihu districts, Rwanda, focused on high malnutrition rates. Agriculture households with children under 5 were sampled using a multistage method. Data, including nutritional status via MUAC and dietary diversity via 24‐h recall, were collected digitally through Kobo Collect. Results The study included 439 respondents, with a mean age of 33 years. Among participants, 359 (81.8%) had low dietary diversity, with Nyamagabe having the highest proportion at 39%. Anemia prevalence was 22.1%, with Karongi having the highest at 10.7%. Factors associated with higher odds of high dietary diversity included the education of the household head (adjusted OR = 6.4, 95% CI: 1.05-39.7), age of women (adjusted OR = 3.03, 95% CI: 1.1-7.8), and wealth status (adjusted OR = 1.66, 95% CI: 0.51-5.4). Conversely, the occupation of women (adjusted OR = 0.13, 95% CI: 0.001-0.19), reading skills (adjusted OR = 0.27, 95% CI: 0.1-0.72), and family size (adjusted OR = 0.63, 95% CI: 0.35-1.1) were associated with lower odds of lower dietary diversity. Conclusion The findings highlight a significant nutritional challenge among Rwandan women, with low dietary diversity, significant rates of anemia, and food insecurity. The study calls for an urgent need for targeted nutritional interventions to improve dietary diversity and address micronutrient deficiencies among women in agriculture to enhance maternal health and child development, thereby contributing to broader public health goals.